The Effect of Tread Pattern Tires on Hard Compound Coefficient Rolling Resistance - Thatit Widya A.P; Muh Nurkoyim Kustanto; Hari Arbiantara B; Franciscus Xaverius K; Robertoes Koekoeh K.W (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2022)
Rolling resistance is the resistance of a wheel that will roll or rotate due to friction between the outer surface of the wheel and the track surface. This study aims to determine the effect of tread patterns on the coefficient of rolling resistance. The tires that will be used in this study are hard compounds with a ratio pattern and tread pattern raised by 2 mm with a tire hardness of 79.5 Ha, and using pressure variations at 30 Psi, 40 Psi, and 50 Psi. Coefficient value rolling resistance is 1.39% with a rolling resistance of 8.05 N. These results are produced by a hard compound with a tread pattern of 2 mm at a pressure of 50 Psi. Meanwhile, the rolling is 2.04% with a rolling resistance of 11.82 N. These results are produced by hard compound tires with a pattern at a tire pressure of 30 Psi.Keywords: compound, tread pattern, rolling resistance